N-Heterocyclic carbene copper-catalyzed direct alkylation of terminal alkynes with non-activated alkyl triflates. Issue 29 (29th March 2017) - Jin, Liqun; Hao, Wangfang; Xu, Jianeng; Sun, Nan; Hu, Baoxiang; Shen, Zhenlu; Mo, Weimin; Hu, Xinquan
Abstract : (NHC)-Cu-catalyzed C(sp)–C(sp 3 ) bond formation has been successfully achieved under mild conditions. Abstract : (NHC)-Cu-catalyzed C(sp)–C(sp 3 ) bond formation has been successfully achieved under mild conditions. Nonactivated alkyl triflates, which could be easily derived from alcohols, were utilized as C–O electrophiles. Mechanistic studies suggested that copper acetylide was the active species. Scale-up reactions further demonstrated the practicality and efficiency of the developed strategy.